The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/mca.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical influence of early follow-up glycosylated hemoglobin levels on cardiovascular outcomes in diabetic patients with ST-segment elevation myocardial infarction after coronary reperfusion

Abstract: This study showed that higher levels of early FU-HbA1c after reperfusion in diabetic patients with STEMI were associated with increased 12-month MACE, suggesting continuous serum glucose level control even after reperfusion is important for a better outcome. FU-HbA1c seems to be a useful marker for predicting clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Results from previous studies were controversial [3,8,[10][11][12][13][14]. Considering the different management and treatment strategies [15], the effects that high HbA 1c level have on STEMI patients might differ from other types of CAD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies were controversial [3,8,[10][11][12][13][14]. Considering the different management and treatment strategies [15], the effects that high HbA 1c level have on STEMI patients might differ from other types of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…After scanning the titles, abstracts, reading full texts and hand searching the reference lists of candidate articles, we finally got 19 prospective studies including a total of 35,994 STEMI patients to evaluate the associations between HbA 1c level and their in-hospital, 30-day and long-term mortality. Among these studies, there were 13 studies from Asia [3,8,10,12,13,[23][24][25][26][27][28][29][30], 5 from Europe [11,[31][32][33][34] and 1 from North America [35]. Detailed information of the eligible studies was shown in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…37 Similarly, higher levels of follow-up HbA 1c are associated with increased 12-month MACE rates in patients with diabetes and STEMI after reperfusion. 50…”
Section: Resultsmentioning
confidence: 99%
“…37 Similarly, higher levels of follow-up HbA 1c are associated with increased 12-month MACE rates in patients with diabetes and STEMI after reperfusion. 50 In conclusion, patients with some form of glucose intolerance are at higher risk of mortality after an ACS than those with normal glucose tolerance. Admission plasma glucose plays a role in predicting adverse events, especially in subjects with previously unknown diabetes.…”
Section: Question 1: Are Admission Glucose and Glycated Haemoglobin Pmentioning
confidence: 88%